2020
DOI: 10.1093/infdis/jiaa548
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic Membrane Vesicles of Group B Streptococcus Promote Infection

Abstract: Group B Streptococci (GBS) are β-hemolytic, Gram-positive bacteria associated with fetal injury, preterm birth, spontaneous abortion, and neonatal infections. A key factor promoting GBS virulence is the β-hemolysin/cytolysin, a pigmented ornithine rhamnolipid (also known as granadaene) associated with the bacterial surface. A previous study indicated that GBS produce small structures known as membrane vesicles (MVs), which contain virulence-associated proteins. Here, we show that GBS MVs are pigmented and hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 44 publications
2
33
0
Order By: Relevance
“…The presence and abundance of sialidase was variable: the ST-1 and ST-17 MVs all contained sialidase, but the ST-12 MVs lacked it. In two prior studies examining GBS MVs produced by a ST-7 strain, A909, neither C5a peptidase nor sialidase were identified (14,15), further highlighting differences across strains. However, we cannot rule out the possibility that the abundance of these virulence factors was beneath the detection limit in those studies.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The presence and abundance of sialidase was variable: the ST-1 and ST-17 MVs all contained sialidase, but the ST-12 MVs lacked it. In two prior studies examining GBS MVs produced by a ST-7 strain, A909, neither C5a peptidase nor sialidase were identified (14,15), further highlighting differences across strains. However, we cannot rule out the possibility that the abundance of these virulence factors was beneath the detection limit in those studies.…”
Section: Discussionmentioning
confidence: 88%
“…Current knowledge regarding GBS derived MVs is restricted to one clinical strain (14,15) and hence, we sought to examine MV production and composition in a set of clinical strains with different traits. While no clear association was observed between clinical phenotype and the production or composition of MVs, we have demonstrated that the GBS MV proteome is STdependent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations